Komunikasi Alquran: Bahasa sebagai Media Ekspresi Verbalistik - AULIA, ALY (Universitas Muhammadiyah Yogyakarta, 2013)
Language is a symbol or emblem of the most widely used. primary means to express thoughts, feelings, intentions, and goals. This is done by using words to represent different aspects of reality. Language can represent a lot of facts, phenomena, and even something abstract that is around humans. No exception to the Qur’an, the holy book would not want to use language as a medium. In this study described how language functions with a series of words to express the essence, meaning, form, something that is not there, past, present, future, and other things that certainly can not be separated from the context of the discourse with all its elements. Keyword: Communication of the holy Quran, Language, and Media